TREATMENT IN KHANABAD-WELLNESS AND RECREATION TO THE HISTORY OF THE FORMATION AND DEVELOPMENT OF TOURISM RELATED COMMENTS - Madaxanov, Akmal; Madaxanov, Akbarjan; Xalilov , Izzatillo (Medical science of Uzbekistan, 2023)
The article covers the most remote territory of the Republic of Uzbekistan located-treatment in Khanabad-health-improving and recreational tourism in its formation and development, the city and its immediate surroundings existedinformation that natural healing factors played an important role will be brought. Their love for their native city, with intelligence, is here selflessness of people creating a unique wellness complex historical information about their work is outlined.